EFFECTIVENESS OF THE IMPLEMENTATION OF COOPERATIVE LEARNING MODEL OF TPS-SNOWBALL THROWING TYPE IN MATHEMATICS LEARNING OF CLASS VII STUDENT AT SMPN 5 MAROS - Sukma Fratiwi supu (Universitas Negeri Makassar, 2018)
The study aims at describing the effectiveness of cooperative learning model of TPS-Snowball Throwing type in Mathematics learning of class VII students at SMPN 5 Maros. The study is pre-experiment research. The experiment unit of the study was all students in class VII at SMPN 5 Maros of academic year 2016/2017 which consisted of 9 parallel classes and the class which had the treatment was class VII1 chosen by employing simple random sampling technique. Data were collected by using observation sheet instrument of learning implementation, observation sheet of students’ activities, learning test, observation sheet of students’ affective aspect, and students’ response questionnaire on learning. Data were analyze by employing descriptive analysis and inferential analysis used one sample t-test.The result of the study reveal that the students’ activities in learning are in active category with the mean 3.29 of maximum score 4, the learning result of students’ cognitive aspect was in high category with the mean 87.91 of maximum score 100, and deviation standard is 6.72, the classical completeness is 94 %, the mean normalized gain of learning result is in high category , the learning result of students’ affective aspect is in high category with the mean 81 of maximum score 100, the students’ response on learning is in Tended to be Positive category with mean 3.19 of maximum score 4. In general, the conclusion is the cooperative learning model of TPS-Snowball Throwing type is effective to be applied in Mathematics learning in class VII students at SMPN 5 Maros